Enantioselective Synthesis of Caprolactam and Enone Precursors to the Heterocyclic DEFG Ring System of Zoanthenol. Issue 12 (19th April 2016) - Bagdanoff, Jeffrey T.; Behenna, Douglas C.; Stockdill, Jennifer L.; Stoltz, Brian M.
Abstract: The enantioselective synthesis of both caprolactam and enone synthons for the DEFG ring system of zoanthenol are described. The evolution of this approach proceeds first through a synthesis using the chiral pool as a starting point. Challenges in protecting‐group strategy led to the modification of this approach beginning with (±)‐glycidol. Ultimately, an efficient approach was developed by employing an asymmetric hetero‐Diels–Alder reaction. The caprolactam building block can be converted by an interesting selective Grignard addition into the corresponding enone synthon. Addition of a model alkyne provides support for the late‐stage addition of a hindered alkyne to the caprolactam building block. Abstract : The syntheses of two synthons for the heterocyclic core of the marine alkaloid zoanthenol are described. These fragments can be generated in a divergent manner from the product of an enantioselective hetero‐Diels–Alder reaction. Judicious selection of protecting groups allows control of a key Grignard reaction to form the enone synthon. The feasibility of the caprolactam as a synthon is validated.